Current research trends on interrelationships of eco-innovation and internationalisation: A bibliometric analysis - Paulius Šūmakaris; Deniss Šceulovs; Renata Korsakienė (Journal of Risk and Financial Management, 2020)
In this paper, bibliometric analysis is conducted on eco-innovation and internationalisation, since in the scientific literature, both research fields have been considered as being interrelated. Although the adoption of eco-innovation and internationalisation are risky processes, they reduce competitive risk and increase performance in a highly competitive business environment. The main objective of this study is to identify current research trends on the interrelationships of eco-innovations and internationalisation as well as the main areas of knowledge and to provide a general overview of research streams that can be classified using by papers, authors and journals found in the Web of Science database. In total, 1677 publications published between 1991 and 2020 related to eco-innovations and internationalisation were taken into consideration. For the visualisation of bibliographic material, VOSviewer software was used. These findings provide valuable insights by revealing the trends and highlighting the possible research streams for future investigations in the field of eco-innovations and internationalisation research.
Keywords: 330; eco-innovation; internationalisation; risk; performance; bibliometric analysis